Red blood cell transfusion in infants and children - Current perspectives - Natasha Ali (Elsevier, 2018)
Children routinely receive packed red blood transfusion when they are admitted in the intensive care unit or undergoing cardiac surgeries. These guidelines aim to summarize literature and provide transfusion triggers exclusively in infants and children.